2021
DOI: 10.1002/eat.23640
|View full text |Cite
|
Sign up to set email alerts
|

A systematic scoping review of research on COVID‐19 impacts on eating disorders: A critical appraisal of the evidence and recommendations for the field

Abstract: Objective Research investigating the effects of COVID‐19 on eating disorders is growing rapidly. A comprehensive evaluation of this literature is needed to identify key findings and evidence gaps to better inform policy decisions related to the management of eating disorders during and after this crisis. We conducted a systematic scoping review synthesizing and appraising this literature. Method Empirical research on COVID‐19 impacts on eating disorder severity, prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
115
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(148 citation statements)
references
References 122 publications
8
115
1
Order By: Relevance
“…These studies have demonstrated that during COVID-19 pandemic people with eating disorders have experienced elevated feelings of stress, fear, and anxiety. At the same time, our study participants did not note any change in their relations with people in their personal networks contrary to some of the other studies of the perceived social support among people with eating disorders during COVID-19 pandemic ( Sideli et al, 2021 ; Linardon et al, 2022 ). Perhaps our participants were able to maintain relationships with people from their personal networks via digital technologies that is why they did not notice any changes in their social networks.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These studies have demonstrated that during COVID-19 pandemic people with eating disorders have experienced elevated feelings of stress, fear, and anxiety. At the same time, our study participants did not note any change in their relations with people in their personal networks contrary to some of the other studies of the perceived social support among people with eating disorders during COVID-19 pandemic ( Sideli et al, 2021 ; Linardon et al, 2022 ). Perhaps our participants were able to maintain relationships with people from their personal networks via digital technologies that is why they did not notice any changes in their social networks.…”
Section: Discussioncontrasting
confidence: 99%
“…They associate these changes with lockdown restrictions. Women also reported that they felt more anxious about their current and future educational and career prospects, which corresponds with studies of emotional wellbeing during COVID-19 pandemic among people with eating disorders ( Sideli et al, 2021 ; Linardon et al, 2022 ). These studies have demonstrated that during COVID-19 pandemic people with eating disorders have experienced elevated feelings of stress, fear, and anxiety.…”
Section: Discussionsupporting
confidence: 60%
“…Future research is needed to examine how the identified prevalence estimates align with estimates for behavioral ED symptoms and confirmed ED diagnoses. Finally, the COVID‐19 pandemic has negatively impacted individuals' ED symptoms (Linardon et al, 2022). Although this impact is likely minimal among the present sample, as few participants (7.27%) completed the HMS post‐COVID onset, the role of COVID‐19 in relation to college students' ED symptoms should be assessed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians from a range of professional backgrounds with varying lengths of experience in EDs participated, allowing for an array of perspectives to be considered. Although clinicians were all based in the UK, the results of this study may be applicable elsewhere, as the COVID-19 pandemic has impacted ED services across the globe and many have had to adopt similar ways of working (e.g., partial closures, virtual treatment delivery) [ 5 , 8 , 43 , 44 ]. All DP services adapted, rather than closed, which is not representative of the wider UK picture, although positively, it highlights the possibility of virtual intensive ED treatment.…”
Section: Discussionmentioning
confidence: 99%